The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12030253
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Meal Inclusion Rate and the Effect of Exogenous Enzymes on Growth Performance of Broiler Chickens

Abstract: The study examined the effect of de-hulled sunflower meal (SFM) inclusion rate and exogenous enzymes (EE) on broilers production performance. A four-feeding phase of pre-starter (1–9 d), grower (10–20 d), finisher (21–28 d) and post-finisher (29–35 d) was used with SFM included as low (BSL) and high (BSH) in all phases. BLS inclusion was 3% throughout phases and BSH inclusion was 7.5%, 10%, 13% and 13.5% for the 4-phases. Each SFM had a negative control (NC) (BSL− and BSH−) and positive (PC) (BSL+ and BSH+) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Therefore, NC and N25 could be economically integrated into the feed formulation for the BW gain comparable to PC. The by-products used in the current study are also readily available all year round and in large quantities in most developing countries (Alshelmani et al, 2021;Mbukwane et al, 2022) While the efficacy of any feed enzyme is based on performance data obtained from feeding trials (Aftab & Bedford, 2018), it is important to note that pre-treatment has been shown to improve digestibility in in vitro studies. For example, pre-treatment of maize-soybean-based diets with probiotics and subsequently, oven drying and pelleting them, has been shown to work and improve growth performance (Yeh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, NC and N25 could be economically integrated into the feed formulation for the BW gain comparable to PC. The by-products used in the current study are also readily available all year round and in large quantities in most developing countries (Alshelmani et al, 2021;Mbukwane et al, 2022) While the efficacy of any feed enzyme is based on performance data obtained from feeding trials (Aftab & Bedford, 2018), it is important to note that pre-treatment has been shown to improve digestibility in in vitro studies. For example, pre-treatment of maize-soybean-based diets with probiotics and subsequently, oven drying and pelleting them, has been shown to work and improve growth performance (Yeh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…They have been explored as the alternative source of protein and energy to replace a portion of soybean meal and maize, respectively (Alshelmani et al, 2021). The main challenges with using nonconventional feedstuffs are the anti-nutritional factors, such as non-starch polysaccharides (NSPs) (Mbukwane et al, 2022). The inclusion of ingredients that are high in dietary fibre in broiler chicken diets has been associated with gut health and growth performance problems (Hamedi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SFM’s β-glucan, like the β-glucans found in cereals, can increase the viscosity of the gut content, which is associated with reduced nutrient absorption and imbalance of the microbiota in the small intestine ( 13 , 14 ). For this reason, NSP-degrading enzymes are used also if SFM-containing diets are provided ( 15 ). The positive effect of this addition on nutrient utilization and production traits has already been demonstrated by numerous studies ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the poultry industry is focused on improving nutrient utilization and disease resistance to reduce indirect costs, improve animal welfare, and reduce the environmental impact of poultry production. Improving poultry production through health and nutrient utilization requires a better understanding of the role of exogenous enzymes (Bischoff, 2011;Mbukwane et al, 2022). Thus, this study aimed to assess the impact of using Labazyme in quail feed on egg production, physiological parameters, and economics.…”
Section: Introductionmentioning
confidence: 99%